Epidemiologia do padrão face curta em escolares do ensino fundamental do município de Bauru -SP - Bastos, Douglas Rezende (2019)
Individuals with short face may present different degrees of severity in vertical deficiency, as well as malocclusions that are difficult to manage. The categorization of vertical deficiency is useful to determine the treatment prognosis. This survey assessed the distribution of ethnically different individuals with vertical deficiency according to three levels of severity, and the determined prevalence of short face pattern. The survey was comprised of 4,409 individuals of Brazilian ethnicity (2,192 females and 2,217 males) enrolled in middle schools in Bauru-SP, Brazil. The criterion for inclusion of individuals with vertically impaired facial relationships was based on excessive lip compression, evaluated under natural light, in standing natural head position with the lips at rest. Once identified, the individuals were classified into three subtypes according to the severity: mild, moderate, and severe. Then the pooled sample was distributed according to ethnical background as White (Caucasoid), Black (African descent), Brown (mixed descent), Yellow (Asian descent). The Chi-square (2) test was used (p<0.05) to compare the frequency ratios of individuals with vertically impaired facial relationships in the total sample and among different ethnicities, according to the three levels of severity and between sexes. It was observed that the prevalence of Face Pattern Short was 3.15%, with a predominance of moderate severity level (2%). The prevalence of Face Pattern Short to mild severity was 1.13% and for severe severity was 0.02%. Caucasians had the highest prevalence of individuals with short face, followed by browns, blacks and yellows. Whites (65.29%) and brown (64.29%) had a prevalence of moderate severity level, while among the yellow (100%) and blacks (100%) prevailed average severity mild level. The only guy who showed severe level of severity was white. There was a higher frequency of females (4.29%) who presented the Face Pattern Short compared to males (2.03%). Both for males (1.26%) and females (2.74%) the severity level that prevailed was moderate. White individuals had the highest prevalence of individuals with short face, followed by browns, blacks and yellows. The prevalence of short face pattern was 3.15% in which 2% and 0.02% belonged to moderate and severe subtypes, respectively.